2022
DOI: 10.1145/3534597
|View full text |Cite
|
Sign up to set email alerts
|

PPGface

Abstract: Recognition of facial expressions has been widely explored to represent people's emotional states. Existing facial expression recognition systems primarily rely on external cameras which make it less accessible and efficient in many real-life scenarios to monitor an individual's facial expression in a convenient and unobtrusive manner. To this end, we propose PPGface, a ubiquitous, easy-to-use, user-friendly facial expression recognition platform that leverages earable devices with built-in PPG sensor. PPGface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“… One-shot motions: One-shot motions are not normally performed continuously, and they are often performed in normal social interactions as well as in the form of psychosomatic tics. The selection process for the one-shot motion artifacts was informed by both anatomy principles 28 and previous work 32 – 34 . In building our dataset, we look at Action Units (AUs) that entail the movement of the head, the eyes (and the adjacent muscles), and the mouth.…”
Section: Methodsmentioning
confidence: 99%
“… One-shot motions: One-shot motions are not normally performed continuously, and they are often performed in normal social interactions as well as in the form of psychosomatic tics. The selection process for the one-shot motion artifacts was informed by both anatomy principles 28 and previous work 32 – 34 . In building our dataset, we look at Action Units (AUs) that entail the movement of the head, the eyes (and the adjacent muscles), and the mouth.…”
Section: Methodsmentioning
confidence: 99%
“…Taniguchi et al confirmed that an earphone-type sensor equipped with a light-emitting diode and a phototransistor can be utilized to measure the shape change of the ear canal caused by tongue movement, which can be used in applications such as music players [18]. Choi et al utilized earphones with a built-in optical heart rate sensor and an accelerometer to acquire changes in facial muscle movement and confirmed that the earphones could detect and recognize seven facial expressions of the user, including anger and surprise [19].…”
Section: Related Work a Hearing Assistance And Enhancement In Hearablesmentioning
confidence: 99%
“…Although it is feasible to infer characteristics of the entire face using only local facial regions, this approach often requires significant power consumption. Notably, previous researches have incorporated sensors into various wearable items such as necklaces [11], headphones [13,46], hats [7], ear-mounted devices [6,8], and eyeglasses [60] to detect facial movements without direct full-face capture. However, the power requirements of these sensors, including RGB cameras and acoustic sensors like microphones and speakers [46,60], are typically too high for continuous operation, limiting their practicality for prolonged use.…”
Section: Introductionmentioning
confidence: 99%